DIGITAL TECHNOLOGIES IN CHILDREN’S ORAL LANGUAGE LEARNING: A CONCEPTUAL NARRATIVE LITERATURE REVIEW OF TEACHER PRACTICES, PEDAGOGICAL CHALLENGES, AND INSTRUCTIONAL RESPONSES IN EARLY CHILDHOOD AND PRIMARY EDUCATION - F. Devi Kurnia; Joko Pamungkas (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
Children’s oral language development is a fundamental component of early literacy, classroom participation, social communication, and later academic achievement. The growing use of digital technologies in early childhood and primary education has created new opportunities for supporting children’s speaking, listening, vocabulary development, storytelling, expressive language, and communicative confidence. However, the pedagogical contribution of digital technologies remains dependent on how teachers design, mediate, assess, and respond to children’s language learning. This article presents a conceptual narrative literature review that maps, integrates, and critically describes theoretical perspectives and empirical findings on the use of digital technologies in children’s oral language learning. The review draws on selected Scopus-indexed studies and relevant theoretical literature on sociocultural theory, scaffolding, pedagogical content knowledge, TPACK, digital play, professional vision, and formative assessment. The analysis identifies four major themes: digital technologies as mediational tools, teacher practices in digitally mediated oral language instruction, pedagogical and institutional challenges, and instructional responses for meaningful digital integration. The findings suggest that digital technologies such as video-recorded performance, SMART boards, e-storybooks, digital drama, robotics-based storytelling, language screening applications, and virtual interactions can support oral language development when embedded in active, dialogic, and teacher-mediated pedagogy. The review concludes that a pedagogy-first approach is needed to ensure that digital technologies are used not as isolated tools, but as resources for scaffolding, dialogue, play, feedback, formative assessment, and children’s active language participation.